Protection internationale du climat et souveraineté étatique - Agnès Michelot (VertigO)
The role of State sovereignty in the development of international climate regime seems unavoidable because it is inherent to modern international law. International environmental law, on the other hand, relies on State sovereignty principle to develop its own objectives. No matter how fragile or weak international law appears in its current climate protection endeavours, it is still generally relevant. The real question is whether the present climate crisis does or could alter the principle of State sovereignty (ie., its definition, implementation, perspectives ). And could we consider that the concept of State sovereignty enhances or, on the contrary, mitigates the climate protection?